A Bibliometric Review of Risk-Taking Propensity Research Trends Patterns and Future Directions - Loso Judijanto (Sciences du Nord Economics and Business, 2025)
Risk-taking propensity is a central construct in understanding human behavior under uncertainty and has attracted sustained scholarly attention across disciplines such as psychology, management, entrepreneurship, health, and decision sciences. Despite the growing volume and interdisciplinary nature of this literature, a comprehensive overview of its intellectual structure, thematic evolution, and future research directions remains limited. This study aims to address this gap by conducting a bibliometric review of risk-taking propensity research using publications indexed in the Scopus database. Bibliographic data were analyzed using VOSviewer to map publication trends, influential authors, institutions, and countries, as well as to identify key research themes through co-authorship, citation, and keyword co-occurrence analyses. The findings reveal that the literature is strongly rooted in psychological and behavioral research, with high risk behavior emerging as a dominant core theme.evolving emphasis on decision-making, risk perception, and cognitive processes. More recent research increasingly links risk-taking propensity to entrepreneurship, innovation, and strategic management, reflecting a shift toward applied and organizational contexts. This study provides a systematic and visualized synthesis of the risk-taking propensity research landscape, offering theoretical insights, practical implications, and guidance for future interdisciplinary inquiry.